PENGETAHUAN TENTANG PENTINGNYA PIJAT OKSITOSIN PADA IBU NIFAS UNTUK MENINGKATKAN PRODUKSI ASI LITERATUR REVIEW - Suhartini; Yudiarsi Eppang; Muliyana; Reskiawati Azis (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2022)
Exclusive breastfeeding is highly recommended to be given to newborns until the age of six months and without breastfeeding assistance. The smooth release of breast milk in nursing mothers is a very important requirement to meet infant nutrition, breast milk is the best nutrition for babies to prevent infection and several other diseases. The decrease in milk production and expenditure in the first days of birth can be caused by a lack of stimulation of the hormones prolactin and oxytocin which play a very important role in the production and secretion of breast milk. Objective: This study was to determine the importance of oxytocin massage in postpartum mothers. is a literature review study and the search for sources used, namely this article uses the literature study method from scientific journals with keyword guidance. Selected scientific journals number 6 journals represent the influence of oxytocin on breast milk production and provide varied information and literature used from 2017-2021. Results: Oxytocin massage is an alternative to overcome the unevenness of breast milk production, oxytocin massage is an attempt to trigger Prolactin and oxytocin hormones after delivery. Conclusion: Based on the analysis that has been done, oxytocin massage is effective for breast milk production, because there is an effect of oxytocin massage on breast milk production, and there is a significant difference between breast milk production before and before treatment